Analisis Estimasi Biaya Dan Efisiensi Penggunaan Semen Instan (Mortar) Vs Semen Konvensional Pada Pekerjaan Dinding Rumah Sederhana (Studi Kasus: (Palopo) - Fitriani Fitriani; Anggel Erpa Erong Pakiding (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Constructing a simple house requires efficient budget planning without compromising structural quality. Wall work is one of the components with the largest volume in house construction. This study aims to compare the direct cost estimates and time efficiency between the use of conventional cement (Portland Cement + Sand) and instant cement (mortar) for wall work (masonry, plastering, and finishing) per 1 m2. The analytical method used is a unit price analysis based on a standard approach in the field and adjusted standards. The results show that although the price of instant cement is higher per bag, its efficiency in terms of work speed, minimizing waste, and neatness of the final result make instant cement a very competitive alternative in terms of total actual construction costs in the field.